Optical Spectroscopy of X-Mega Targets in Carina Nebula - Albacete Colombo, Juan Facundo (2001)
Optical spectroscopy of CPD-59° 2635, one of the O-type stars in the open cluster Trumpler 16 in the Carina Nebula, reveals this star to be a double-lined binary system. We have obtained the first radial velocity orbit for this system, consisting of a circular solution with a period of 2.2999 d and semi-amplitudes of 208 and 273 km s−1. This results in minimum masses of 15 and 11 M? for the binary components of CPD-59° 2635, which we classified as O8V and O9.5V, although spectral type variations of the order of 1 subclass, which we identify as the Struve–Sahade effect, seem to be present in both components. From ROSAT HRI observations of CPD −59° 2635 we determine a luminosity ratio log(Lx/Lbol)≈−7, which is similar to that observed for other O-type stars in the Carina Nebula region. No evidence of light variations is present in the available optical or X-ray data sets.